Morphometric analysis of drainage basins in Lakhwar and adjoining areas of Dehradun and Tehri Garhwal Districts, Uttarakhand, India - Bhatta, SP; Biyani, AK; Dudeja, D (Journal of Nepal Geological Society, 2012)
The drainage basins of Yamuna River and its tributaries near Lakhwar and adjoining areas fall in the frontal Lesser Himalayan terrain belonging to the northwestern part of the Mussoorie Syncline in the Krol Belt. It mainly comprises quartzites,slates, and phyllites. A detailed drainage map was prepared from the topographic maps and the area was divided into ten drainage basins for morphometric analysis. The major tributaries in the study area belong to the fifth order streams. Generally, trellis to subparallel drainage pattern is dominant in the area and dendritic pattern is observed only in third-order streams. These patterns are controlled by local geological structures, lithology, and sudden relief changes. The Yamuna River is frequently meandering while the Aglar River, a major tributary of the Yamuna River, is straight and follows the Aglar Fault. A high bifurcation ratio also confirms the strong structural control on the drainage. Medium to high drainage density values indicate the area to be of mountainous relief developed on weak and jointed bedrock. The basins show more-or-less elongated geometry and perfect degree of adjustment in prevailing conditions. In longitudinal profiles of streams of the study area 2 to 5 knick points are recognised, which can be attributed to sudden relief changes rather than lithological variations in the area. The estimation and detailed interpretation of various morphometric parameters are discussed in the paper. Jour. Nep. Geol. Soc., Vol. 37, 2008, 45-54